2020
DOI: 10.1111/myc.13227
|View full text |Cite
|
Sign up to set email alerts
|

A pseudo‐outbreak of Rhinocladiella similis in a bronchoscopy unit of a tertiary care teaching hospital in London, United Kingdom

Abstract: Outbreaks of fungal infections due to emerging and rare species are increasingly reported in healthcare settings. We investigated a pseudo‐outbreak of Rhinocladiella similis in a bronchoscopy unit of a tertiary care teaching hospital in London, UK. We aimed to determine route of healthcare‐associated transmission and prevent additional infections. From July 2018 through February 2019, we detected a pseudo‐outbreak of R. similis isolated from bronchoalveolar lavage (BAL) fluid samples collected from nine patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
(106 reference statements)
1
7
0
Order By: Relevance
“…Several members of the genus Exophiala are potential agents of human and animal mycoses and for that are considered to be in the Bio Safety Level-2 (BSL-2) group. In this study, together with E. xenobiotica, we found other species associated with clinical cases, including E. oligosperma a sporadic agent of phaeohyphomycosis [81,82], E. phaeomuriformis mentioned in relation to keratitis [83], Rhinocladiella similis recently found in a nosocomial infection [84], and Knufia epidermidis associated with mild skin infections [85].…”
Section: Discussionsupporting
confidence: 51%
“…Several members of the genus Exophiala are potential agents of human and animal mycoses and for that are considered to be in the Bio Safety Level-2 (BSL-2) group. In this study, together with E. xenobiotica, we found other species associated with clinical cases, including E. oligosperma a sporadic agent of phaeohyphomycosis [81,82], E. phaeomuriformis mentioned in relation to keratitis [83], Rhinocladiella similis recently found in a nosocomial infection [84], and Knufia epidermidis associated with mild skin infections [85].…”
Section: Discussionsupporting
confidence: 51%
“…An increased number of fungal species more typically associated with plant pathogenesis are now seen as causative agents of keratitis [ 148 , 149 ]. Fungal outbreaks caused by emergent and rare species are still being recognised in previously unknown patient cohorts [ 150 , 151 ]. Again further work needs to be undertaken to differentiate improvements in diagnosis from increases in infection rates linked directly to climate change.…”
Section: The Spectre Of Newly Arising Fungal Pathogensmentioning
confidence: 99%
“…Among the isolated organisms, Rhodotorula rubra was identified in 3 studies, whereas all other species were reported in only 1 study each. 26,62,87 These included Fusarium solani , 17 Rhinocladiella similis , 58 Phaeoacremonium parasiticum , 19 Aureobasidium spp. 88 In 1 study, both Trichosporon cutaneum and Penicillium spp were isolated.…”
Section: Resultsmentioning
confidence: 99%
“…In 24 studies, the source of contamination was attributed to a defect in the bronchoscope itself. 7,12,16,43,46,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] Bronchoscope segments identified as being defective or damaged included the lumen, the suction valve and channel, the biopsy port and its cap, as well as the biopsy channel itself. Notably, in 1 study the defect at the entry port of the biopsy channel was so significant that it led to a recall of the specific model by the manufacturer.…”
Section: Sources Of Contaminationmentioning
confidence: 99%